Congenital Anomalies among Newborns Admitted in Tertiary Hospital; Iraqi Experience - Naoom, Manal B.; ALSaadi, Yasir I.; Ghalib Yassin, Batool A.; Matloob, Huda Y. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Congenital anomaly is any alteration present at birth of normal anatomic structure and has cosmetic, medical or surgical significance Objective: To determine the pattern of congenital anomalies in neonates admitted to tertiary neonatal care unit and to determine the impact of some factors related to congenital anomalies with and without congenital anomalies. Patients and methods: A case control study was carried out during 6 months period (1St of January to 30th of June 2011). Neonates with and without congenital anomalies admitted to Children Welfare Teaching Hospital were included in the study as a case and control group. Demographic characteristics of both parents and neonates, Consanguinity, Parity, Gestational age, Mode of delivery and type of congenital anomaly were studied. All neonates were examined thoroughly by pediatrician; confirmation of internal defects was done by various imaging modalities Results: Sixty (4.8 %) of 1235 admitted neonates were diagnosed to have congenital anomalies, of whom 70% were males, 86% were term newborn, 55% were delivered by caesarian section, 73.3% were from consanguineous marriage and the mothers of 75% of them were multipara and cardiovascular anomalies was the most common . Conclusions: Surveillance and monitoring of congenital conditions is important for identifying patterns of malformations and planning to improve the outcomes.